Zakat Accounting Practices and Governance Challenges: A Case Study of PSAK 109 Implementation in a Regional BAZNAS - Nur Isnaini; Fadila Wati; Reski Amalia (Journal of Sharia, Law, and Economics, 2025)
This study aims to examine the implementation of zakat accounting practices based on PSAK 109 at BAZNAS Kabupaten Mamuju and to analyze their implications for transparency, accountability, and productive zakat governance. Employing a qualitative descriptive approach with a single case study design, data were collected through semi-structured interviews, participant observation, and document analysis. The analysis focuses on the recognition, measurement, presentation, and disclosure of zakat, infaq/sadaqah, and amil funds, as well as the reporting of productive zakat programs.The findings indicate that BAZNAS Kabupaten Mamuju has implemented basic zakat accounting procedures, particularly cash-based transaction recording and internal fund summaries. However, compliance with PSAK 109 remains partial, as the institution has not prepared a complete set of financial statements, including the statement of financial position, statement of changes in managed assets, cash flow statement, and notes to the financial statements. This incomplete reporting limits transparency and weakens accountability to stakeholders. Although productive zakat programs have generated positive short-term outcomes in supporting beneficiaries’ economic activities, the absence of integrated accounting and monitoring mechanisms constrains the evaluation of long-term sustainability and social impact. The study concludes that PSAK 109 should be understood not merely as a technical accounting standard but as a governance instrument that supports accountability and trust in zakat institutions. Strengthening compliance, particularly in disclosure and integration with productive zakat reporting, is essential to enhance institutional credibility and the effectiveness of zakat as an instrument of Islamic social finance.